1975
DOI: 10.1115/1.3443302
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-Crack Growth in an X-65 Line-Pipe Steel at Low Cyclic Frequencies in Aqueous Environments

Abstract: The effects of salt and distilled water environments on fatigue-crack growth rales have been evaluated for an X-65 line-pipe steel. Tests were conducted over a frequency range between 10 and O.Ol Hz, under conditions of cathodic potential and free corrosion. A distinct pattern in the functional dependence of growth rates on AK and frequency has been found. Maximum environmental enhancement of growth rates was SO times that of air at a cathodic potential of ~1.04V, and 10 times that of air at a free-corrosion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
3

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(33 citation statements)
references
References 21 publications
5
25
0
3
Order By: Relevance
“…[1363] schlagen Wei u. Simmons [1366] vor, die Anteile der rein mechanischen Ermüdung, der eigentlichen Korrosionsermüdung und der Spannungsrißkorrosion zur Rißfortschrittsrate aufzusummieren. 6.69 (a)).…”
Section: Rißfortschritt Bei Spannungsrißkorrosionunclassified
“…[1363] schlagen Wei u. Simmons [1366] vor, die Anteile der rein mechanischen Ermüdung, der eigentlichen Korrosionsermüdung und der Spannungsrißkorrosion zur Rißfortschrittsrate aufzusummieren. 6.69 (a)).…”
Section: Rißfortschritt Bei Spannungsrißkorrosionunclassified
“…This lack of a threshold is observed in the work of Vosikovsky [13], in which hydrogen assisted growth dominates due to the application of a cathodic potential.…”
Section: Environmental Crack Growth In Ferritic Steelsmentioning
confidence: 88%
“…For example, in the work of Thorpe et al , it was found that crack growth rates in BS4360 50D steel in seawater were significantly enhanced at a lower frequency, but at a higher frequency, crack growth rates were found to be similar to those measured in an air environment. A similar phenomenon was also reported by Vosikovsky for X65 pipeline steel tested in 3.5% salt water . A higher load frequency was also reported to have negligible effects on crack growth rates in 12Ni‐5Cr‐3Mo maraging steel tested in 3% sodium chloride solution .…”
Section: Introductionmentioning
confidence: 94%